IMPLEMENTATION OF THINK PAIR SHARE (TPS) TO IMPROVE STUDENT’S LEARNING ACTIVENESS IN TEACHING WRITING AT THE SECOND GRADE OF SMAN 1 KURIPAN - Muhamad Suhaili (Journal of English Education and Literature, 2024)
This research was conducted based on the researcher's observations.The aim of this research is to describe and find out how think pair share is implemented to increase student learning activities in students' writing skills, increase student activity, student responses, student learning outcomes and describe the obstacles that occur during the learning process using Think Pair Share. Pair Share (TPS) Learning. TPS is designed to increase students' sense of responsibility towards the lesson itself and others. The type of research carried out in this research is a pre-experimental design using a "one-group pretest-posttest design", The sample in this research was all class XI students a sample of 30 students. The research instruments used to collect data include: student activity observation sheets, pre-test and post-test sheets provided, and questionnaires. The data analysis method used in discussing the results of this research is a quantitative descriptive method. Based on the research results, a large percentage of class completion was obtained from the pre-test result 16% and increased to 83% from the post-test results. The increase in pre-test to post-test learning outcomes was caused by the implementation of the Think Pair Share type cooperative learning model in cause and effect subjects which was carried out well and ran smoothly. Student activity from observations showed a percentage of 20% at meeting 1 and increased to 51% at meeting 2. The increase in student activity occurred because in teaching and learning activities students were required to be active in work groups and be responsible. the lesson itself and so on. The Think Pair Share type cooperative learning model received a very good response from students, this was shown by a percentage of 75%. Thus, it can be concluded that the Think Pair Share type cooperative learning model can improve student learning outcomes in cause and effect subjects.